Prognostic factors in chronic obstructive pulmonary disease - Górecka, Dorota (Przewodnik Lekarza/Guide for GPs, 2006)
Chronic obstructive pulmonary disease (COPD) is one of the most prevalent chronic diseases in the world. In developed countries it is mainly caused by smoking. COPD became one of the most common causes of mortality and important cause of morbidity. We observe with concern a steep increase in mortality due to COPD during last 20 years. A generalised character of COPD is now recognised. For this reason new prognostic factors have been developed recently. A new index BODE encompasing not only lung component (FEV1) of COPD but also body mass index, dyspnoea and exercise tolerance was proposed. It helps not only to better prognose survival but also recurrent hospitalizations and may be used to measure effects of medical intervention.